1995
DOI: 10.1172/jci118169
|View full text |Cite
|
Sign up to set email alerts
|

Detection of platelet-derived growth factor (PDGF)-AA in actively healing human wounds treated with recombinant PDGF-BB and absence of PDGF in chronic nonhealing wounds.

Abstract: Some human chronic dermal wounds treated with recombinant platelet-derived growth factor-BB (rPDGF-BB) show increased healing coupled with fibroblast activation and granulation tissue formation. To determine whether endogenous PDGF is associated with healing and nonhealing dermal ulcer phenotypes, we developed monoclonal antibodies capable of recognizing the three isoforms of PDGF, AA, AB, and BB dimers, and capable of discriminating between two alternatively spliced A chain transcripts. We detected little PDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
138
0
5

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(151 citation statements)
references
References 50 publications
8
138
0
5
Order By: Relevance
“…Extraction of PDGF from human skin after injection with PDGF-B/Ad5 in this study demonstrated that PDGF isoforms are indeed expressed at higher levels than in LacZ/Ad5-transduced samples. Further, we have shown that the adenoviral transfer of PDGF-B not only induced PDGF-A, but also PDGF-R␣ expression in fibroblasts, which is in accordance with a previous report about the induction of native PDGF-A by exogenous PDGF-B (Pierce et al, 1995). Therefore, fibroblasts may amplify the effects of PDGF-B through PDGF receptors expressed on these cells.…”
Section: Nesbit Et Alsupporting
confidence: 92%
See 2 more Smart Citations
“…Extraction of PDGF from human skin after injection with PDGF-B/Ad5 in this study demonstrated that PDGF isoforms are indeed expressed at higher levels than in LacZ/Ad5-transduced samples. Further, we have shown that the adenoviral transfer of PDGF-B not only induced PDGF-A, but also PDGF-R␣ expression in fibroblasts, which is in accordance with a previous report about the induction of native PDGF-A by exogenous PDGF-B (Pierce et al, 1995). Therefore, fibroblasts may amplify the effects of PDGF-B through PDGF receptors expressed on these cells.…”
Section: Nesbit Et Alsupporting
confidence: 92%
“…PDGF-B increases production of fibronectin in cells (Allen-Hoffmann et al, 1990) and enhances collagen synthesis as part of the wound-healing response (Pierce et al, 1995). We hypothesized that the phenotype induced in vivo by PDGF-B in fibroblasts is due to the up-regulation of integrin ␣5 and ␣2 subunits, which, in turn, increase fibronectin and collagen production.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…DOI: 10.1038/sj/gt/3301697 angiogenic growth factors from macrophages and keratinocytes and its impairment leads to a delay in skin repair. [7][8][9][10][11] One of the essential growth factors which are involved in the angiogenetic process in the wounded tissues is vascular endothelial growth factor (VEGF), 12 which promotes proliferation and migration of endothelial cells resulting in the formation of a capillary network which is an essential requisite for the healing process.…”
Section: Healing Is Concomitant With An Increase Of Production Of Andmentioning
confidence: 99%
“…The formation of new blood vessels provides a route for oxygen and nutrient delivery, as well as a conduit for components of the inflammatory response. Healing is concomitant with an increasing release of angiogenic growth factors from macrophages and keratinocytes and its impairment leads to a delay in skin repair [3,4,5,6,7]. Vascular endothelial growth factor (VEGF) is one of the most potent angiogenic cytokines which promotes all steps in the angiogenic cascade [8].…”
Section: Introductionmentioning
confidence: 99%